2006
DOI: 10.1038/sj.ejcn.1602513
|View full text |Cite
|
Sign up to set email alerts
|

Phytate intake and molar ratios of phytate to zinc, iron and calcium in the diets of people in China

Abstract: Objective: To assess the phytate intake and molar ratios of phytate to calcium, iron and zinc in the diets of people in China. Design: 2002 China Nationwide Nutrition and Health Survey is a cross-sectional nationwide representative survey on nutrition and health. The information on dietary intakes was collected using consecutive 3 days 24 h recall by trained interviewers. Subjects: The data of 68 962 residents aged 2-101 years old from 132 counties were analyzed. Results: The median daily dietary intake of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 38 publications
7
98
2
1
Order By: Relevance
“…It is interesting to note the very low phytate to calcium molar ratio for all infant cereals analyzed; apparently phytate could not compromise Ca availability since the critical value for which the absorption of calcium is compromised has been reported to be > 0.24 [4] . Three of the four infant cereals analyzed showed a phytate to zinc molar ratio above 12, a value implicated in interference with zinc bioavailability in humans [22,23] .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is interesting to note the very low phytate to calcium molar ratio for all infant cereals analyzed; apparently phytate could not compromise Ca availability since the critical value for which the absorption of calcium is compromised has been reported to be > 0.24 [4] . Three of the four infant cereals analyzed showed a phytate to zinc molar ratio above 12, a value implicated in interference with zinc bioavailability in humans [22,23] .…”
Section: Discussionmentioning
confidence: 96%
“…Inositol phosphates were extracted from the different samples with 0.5 mol/L HCl at room temperature for 2 h. Because of the high binding capacity of inositol pentaphosphate (IP5) and inositol hexaphosphate (IP6) to minerals, we consider the sum of IP5 and IP6 to determine phytate content [4,13] . The molar ratios of phytate to iron, calcium, and zinc were calculated as the millimoles of phytate present in the sample divided by the millimoles of iron, calcium, and zinc present in the sample, respectively.…”
Section: Inositol Phosphate Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO normative requirements 29 of people with different bioavailability were used to assess the inadequacy of zinc intake. The percentage of people with zinc intake below the WHO normative requirement at different phytate/zinc molar ratios was calculated [30][31][32] . The estimation of zinc deficiency is based on zinc inadequacy and not any biochemical markers.…”
Section: Estimation Of Populations With Iron and Zinc Deficienciesmentioning
confidence: 99%
“…Seeds including cereals, legumes and nuts all contain phytate with concentrations ranging from 5 to 50 g per kg [8]. This presents a nutritional problem, as phytate can chelate ions with biological functions including zinc and iron [2,9]. It has also been suggested that phytate could form non-digestible complexes with exogenous protein sources and endogenous proteins involved in digestion, causing a reduction in growth in humans [10,11].…”
Section: Introductionmentioning
confidence: 99%